2002
DOI: 10.1046/j.1471-0528.2002.01462.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised study of misoprostol and gemeprost in combination with mifepristone for induction of abortion in the second trimester of pregnancy

Abstract: Two hundred milligrammes of mifepristone followed 36-48 hours later by either vaginal gemeprost or misoprostol is a highly effective way of inducing abortion in the second trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…In our study, mean age of patients in group 1 was 25.77 ± 4.62 years, which was similar to other studies. 7,8,9 Mean parity of group 1 was 2.13 ± 1.34, which corresponds to that of study by Neha Agarwal et al in 2014. 10 In our study, mean gestational age was 15.5 ± 2.85 and 15.72 ± 2.75 in group 1 and group 2, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, mean age of patients in group 1 was 25.77 ± 4.62 years, which was similar to other studies. 7,8,9 Mean parity of group 1 was 2.13 ± 1.34, which corresponds to that of study by Neha Agarwal et al in 2014. 10 In our study, mean gestational age was 15.5 ± 2.85 and 15.72 ± 2.75 in group 1 and group 2, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Mifepristone, a progesterone receptor antagonist, is effective in shortening the induction to abortion interval when used in combination with prostaglandins, but it is expensive. 1,2 Recent reports have demonstrated that misoprostol, a synthetic prostaglandin E 1 analogue, is a promising alternative prostaglandins. 3 -7 It is stable at room temperature and widely available, but its adverse effects, such as fever, nausea, vomiting and abdominal pain, are still of concern.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] They have also been compared with other different dosage protocols of misoprostol which has got significant value regarding the usage of Mifepristone as cervical ripening and abortificient ability.…”
Section: Discussionmentioning
confidence: 99%